2012
DOI: 10.1590/s0100-67622012000400010
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do fogo na produção de frutos de Qualea parviflora Mart. (Vochysiaceae) em cerrado sensu stricto

Abstract: -Among the many effects caused by fires on native species of the Cerrado, the change in fruit production has been highlighted, since it results directly in the maintenance of local populations. The objective of this study was to investigate the effect of a prescribed burning on fruit set of Qualea parviflora Mart. in a cerrado sensu stricto area in Brasília-DF. Two areas of cerrado were studied, one submitted to biennial prescribed burnings in August (burned) and one fire protected for 14 years (control). In e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…However, studies showed that fire events tend to increase the importance of vegetative reproduction in comparison to sexual reproduction (Hoffmann 1998, Silva et al 2009). Palermo & Miranda (2012) observed that no flowers were produced by Qualea parviflora Mart. plants in the burned area, one year after a fire event, suggesting that this species may require more than a year to return to the normal reproductive cycle.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies showed that fire events tend to increase the importance of vegetative reproduction in comparison to sexual reproduction (Hoffmann 1998, Silva et al 2009). Palermo & Miranda (2012) observed that no flowers were produced by Qualea parviflora Mart. plants in the burned area, one year after a fire event, suggesting that this species may require more than a year to return to the normal reproductive cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Mart. and by Palermo () for Q. parviflora . The reduction in fruit loss for those located between 1 and 2 m and between 2 and 3 m suggests a possible effect of a longer period of high temperatures.…”
Section: Discussionmentioning
confidence: 91%
“…Reduced or absent production of reproductive structures in the first year after fires has also been reported for Qualea parviflora Mart. (Palermo & Miranda ), Stryphnodendron adstringens (Mart.) Coville (Felfili et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations